Communication network array signal synchronous transmission method based on Gaussian fuzzy algorithm - Zhong, Jingxiang (Wireless networks, 2022)
In wireless sensor network communication system, the interference caused by random spread spectrum leads to poor communication quality and high bit error rate of communication network array signals. The invention provides a wireless sensor network communication network array signal synchronization transmission algorithm based on Gaussian fuzzy algorithm. Wireless sensor network communication channel model is established within the building and code interference suppression algorithm, using a Gaussian blur algorithm for array signal synchronization control, communication network and the communication network of array signal multipath structure harmonic balance equation, the structure and design of the matched filter detector, implements the communication network optimization of array signal synchronous transmission. The simulation results show that the algorithm can realize the synchronous transmission of the communication network array signals in the wireless sensor network communication, greatly improve the output SNR, greatly reduce the bit error rate of the wireless sensor network communication system, and improve the communication quality and performance.